The Preventive Role of Regular Physical Activity in Non-Specific Low Back Pain Among Physically Active Adults – A Literature Review - Bogdan , Klaudia; Jankowski, Mikołaj; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria; Olszówka, Magdalena; Dziugieł, Sonia (Quality in Sport, 2026)
Background. Non-specific low back pain (NSLBP) is one of the most prevalent musculoskeletal disorders and a leading cause of disability among adults worldwide. Although physically active individuals are generally considered healthier, they remain susceptible to NSLBP, particularly when training loads are improperly managed or recovery is insufficient. Contemporary clinical guidelines increasingly emphasize non-pharmacological approaches, especially physical activity, as a cornerstone of NSLBP prevention. Aim. The aim of this narrative literature review was to evaluate the preventive role of regular physical activity in non-specific low back pain, with particular emphasis on physically active and recreationally active adults. Materials and Methods. A narrative review of the literature was conducted using the PubMed and Scopus databases. Peer-reviewed articles published between 2015 and 2024 were analyzed, including systematic reviews, meta-analyses, randomized controlled trials, and international clinical guidelines. Studies focusing on specific spinal pathologies or postoperative populations were excluded. Results. The analyzed evidence consistently indicates that regular physical activity is associated with a reduced risk of NSLBP onset and recurrence. Aerobic exercise, resistance training, and core stabilization programs were shown to improve spinal stability, functional capacity, and quality of life, while reducing pain-related disability. Multimodal exercise programs demonstrated the most favorable preventive outcomes. Conclusions. Regular physical activity plays a crucial role in the prevention of non-specific low back pain among physically active adults. Appropriately prescribed aerobic exercise, resistance training, and core stabilization exercises should be incorporated into preventive strategies aimed at reducing the burden of NSLBP.